A bismuth oxide/graphene oxide nanocomposite membrane showing super proton conductivity and low methanol permeability. Issue 2 (24th October 2018) - Liu, Bailing; Cheng, Dongming; Zhu, Haotian; Du, Jing; Li, Ke; Zang, Hong-Ying; Tan, Huaqiao; Wang, Yonghui; Xing, Wei; Li, Yangguang
Abstract : A new super proton-conducting H6 Bi12 O16 /GO membrane with high chemical and thermal stability was synthesised via a vacuum-assisted filtration method. Abstract : Proton exchange membrane fuel cells are still limited as state-of-art proton exchange membranes perform poorly at high and low temperature and are easily damaged by harsh electrochemical conditions such as reactive peroxide species. One effective solution to this issue is to develop new types of proton conductive materials that are capable of working in a broad temperature range. A simple vacuum-assisted filtration method is employed to obtain a well-ordered new proton-conducting membrane by immobilizing nanosized bismuth oxide clusters [H6 Bi12 O16 ] (NO3 )10 ·6(H2 O) H6 Bi12 O16 onto graphene oxide (GO) supports (named as H6 Bi12 O16 /GO). H6 Bi12 O16 /GO is stable in acidic media and has high proton conductivity over the temperature range from −40 to 80 °C. The proton conductivity of the H6 Bi12 O16 /GO membrane is 0.564 S cm −1 at 80 °C in aqueous solution (in plane), and 0.1 S cm −1 at 80 °C and 97% RH (out of plane), respectively. Without loss of high proton conductivity, the membrane also exhibited 100-fold lower methanol permeability than a Nafion 117 membrane. Moreover, H6 Bi12 O16 /GO displayed good catalytic decomposition of hydrogen peroxide and superior humidity response and recovery properties. These advantages mean that H6 Bi12 O16 /GO holds great promise as a solid-state electrolyte that can potentially be applied in energy conversion devices in the future.